Investigation of Water-Soluble Vitamins in Sumac (Rhus Coriaria L.) Grown in Different Regions and Subjected to Different Preservation Methods - Ali, Haval; Karatas, Fikret; Özer, Dursun; Saydam, Sinan (My University, 2024)
The amounts of water-soluble vitamins in unoiled and oiled sumac samples grown in different regions were determined by HPLC. For this purpose, the ground samples were divided into two parts, one part was oiled, while the other part was kept as is for six months and then analyzed. It was found that the amounts of ascorbic acid, thiamine, riboflavin, nicotine amide, nicotinic acid, pantothenic acid, pyridoxine, folic acid and cyanocobalamin in sumac samples kept for six months unoiled varied between 22.2 ± 1.1 - 48.8 ± 1.9, 38.9 ± 1.7 - 123.1±4.1, 123.8 ± 7.3 - 404.7 ±14.6, 5.8±4.5 - 203.8±8.5, 527.9±10.9 - 993.8±20.4, 216.7±7.7 - 575.4±13.7, 72.2±3.8 - 244.2±9.2, 359.2±14.1 - 612.8± 19.5, 43.0±2.2 - 108.8±4.8 ?g /g dw, respectively. The difference between the amounts of water-soluble vitamins in oiled and unoiled sumac samples for all regions is statistically significant (P<0.05). It was also found that the vitamin loss in oiled samples were less than unoiled samples.
Keywords: Preservation; Rhus coriaria L; Water soluble vitamins